Controllable Band Alignment Transition in InSe–MoS2 Van der Waals Heterostructure. Issue 7 (18th April 2018) - Chen, Xi; Lin, Zheng‐Zhe; Ju, Ming
Abstract : Van der Waals (vdW) heterojunctions with type‐II band alignment, in which electrons and holes are localized in distinct layers, play a central role in optoelectronic devices and solar cells. The present study analyzes a type‐I→II band alignment transition in InSe–MoS2 vdW heterostructure, proposed to be controlled via changing interlayer distance or applying perpendicular external electric field. The band position shift of InSe relative to that of MoS2 attributes to a surface polarization mechanism. Changing band offset into type II facilitates possible use and allows greater flexibility for band engineering of InSe–MoS2 heterostructure in optoelectronic and solar energy applications. The present findings provide theoretical guidance to a new approach to improve the optoelectronic properties of vdW heterostructures. Abstract : InSe–MoS2 Van der Waals (vdW) heterostructure presents controllable type‐I→II band alignment transition by changing interlayer distance or applying perpendicular external electric field. The shift of the band position of InSe relative to that of MoS2 is attributed to a surface polarization mechanism. Changing band offset into type II facilitates possible use and flexible band engineering in optoelectronic and solar energy applications.